Learning Outcomes in Scandinavian Education through the Lens of Elliot Eisner. Issue 5 (28th July 2020) - Prøitz, Tine S.; Nordin, Andreas
ABSTRACT: Discursively learning outcomes have been embedded within an education-policy context characterised by a shift from teaching to learning. In the dominant education policy discourse, learning outcomes have come to play an important role in education whose emphasis is more on product than process, which by its critics have been characterised as scientific management. Calls have been made to reconsider alternative interpretations of learning outcomes and a renewal of older perspectives on learning outcomes such as in Eisner's works. The article examines the concept of learning outcomes, as interpreted in education policy, and discusses it within Eisner's framing of teaching and learning. Analysing policy developments and the introduction of learning outcomes in two Scandinavian countries, we ask what is taken for granted in the interpretation of learning outcomes. The analysis contributes to a widened narrative on what education could be about by illuminating alternative ways of interpreting and conceptualising learning outcomes in education.